New Function of Seaports: Logistics and Distribution - Jakomin, Igor (Promet - Traffic&Transportation, 2003)
The globalization process occurs in all the spheres of ourlife and its quantitative and spatial dimensions affect theworld’s development. These trends lead the enterprises to concentrateon their core business and outsource some auxilimy oradditional parts of their production or se1vices. It is vital for theoperation in such conditions that the logistics functionssmoothly and reliably in all its segments.To provide an answer to the given hypothesis, I have dealtwith all the major questions linked to the phenomenon of seaportsand their role in the development of new logistical anddistributional function.